Perforating wound of the left eye in a 21-year-old patient with preservation of full visual acuity - Szala, Klaudia; Woszczek, Dawid; Górska, Aleksandra; Sirek, Sebastian; Wyględowska-Promieńska, Dorota (Klinika Oczna / Acta Ophthalmologica Polonica, 2025)
Eye injuries represent 10-15% of all ocular diseases, with over 55 million cases reported annually due to household, occupational, sports, and automotive accidents. The World Health Organization (WHO) identifies eye injuries as a leading cause of visual impairment. Timely intervention is critical, as complications such as infections, hemorrhages or changes in intraocular pressure can result in irreversible damage to the visual system. A 21-year-old patient presented to the Emergency Room with a left eye injury caused by a metallic foreign body during sheet metal cutting without protective equipment. The object penetrated the lower eyelid, conjunctiva, and sclera from the nasal side. Visual acuity in the injured eye was 5/5 without correction, and intraocular pressure was 16 mmHg. A scleral wound at the 10 o’clock position was identified via slit-lamp examination and a CT scan ruled out intraocular foreign bodies. The patient was treated with intravenous broad-spectrum antibiotics and underwent surgical intervention. Surgery was undertaken under local anesthesia and involved revision of the conjunctival and scleral wound, followed by suturing of the scleral, conjunctival, and lower eyelid wounds. Postoperative outcomes included preserved visual acuity and stable intraocular pressure. Early diagnosis and prompt treatment can often save vision and improve quality of life. Public education on eye injury first aid and access to specialized care are essential to reduce the burden of visual impairment.